Analysis on the current status and influencing factors of building energy consumption in China - YULONG, Cheng; MORGUN, Alla (Ways to Improve Construction Efficiency, 2025)
Based on the current status of building energy consumption in China, this paper analyses the main influencing factors of building energy consumption and explores strategies and measures to reduce building energy consumption. Through literature review and data analysis, the study found that due to the accelerated level of social and economic development, the total energy consumption of China's buildings has continued to grow. After the country raised energy-saving standards and adopted energy-saving technologies, the energy intensity showed a downward trend. China has a vast territory, with significant climate differences between the east, west, south and north, and the energy demand for heating in winter and cooling in summer is different. The main influencing factors of building energy consumption include the level of economic development. Building energy consumption is positively correlated with the level of economic development, but the growth rate of energy consumption is often lower than the economic growth rate, which reflects the effect of technological progress and energy-saving measures. Population size and urbanization. China's continuously growing population size and rapid urbanization process have led to the continuous expansion of building scale and the continuous increase in building energy demand. Climate conditions. The northern region is cold in winter, and heating energy consumption accounts for a large proportion of building energy consumption; while the southern region is hot in summer, and cooling energy consumption is relatively high. Building scale and structure. The size of the building and the building structure system have a direct impact on energy consumption. The larger the building area, the higher the total energy consumption. There are also energy-consuming equipment and technology. The promotion and application of energy-consuming equipment has significantly reduced building energy consumption. Through the above analysis, measures to improve energy efficiency are proposed, such as improving the policy and regulatory system, promoting energy-saving technologies and products, optimizing building design and construction, and strengthening operation management and maintenance. The research results can provide a reference for the formulation of building energy-saving policies and measures.